Extranjeros en la propia patria - Juan N. Seguín : los tejanos y las guerras de independencia de México y Texas - Kökény, Andrea (Acta Hispanica, 2011)
The paper analyses how the Mexican Texans (téjanos) related to the Mexican War of Independence, what role thy played in the borderland region, and why some of them decided to support the Anglo-American immigrants in their War of Independence against Mexico in 1836. The study is primarily based on the results of American historiography and the memoirs and correspondence of one of the most influential and controversial téjanos, Juan Nepomuceno Seguin. He was an outspoken critic of the centralist policies of Santa Anna, the Mexican president and supported the Texans’ demand for more self-government. He fought in the regular army of Texas against the Mexicans, and after gaining independence was elected to the Senate of the new republic and twice won election as mayor of San Antonio. Then, however, as thousands of American newcomers arrived in Texas, he gradually became „a foreigner in his native land" and was forced to leave his homeland andflee to Mexico.